Temporal variation in p38-mediated regulation of DUX4 in facioscapulohumeral muscular dystrophy - Rajanikanth Vangipurapu; Jonathan Oliva; Amelia Fox; Francis M. Sverdrup (Scientific Reports)
Abstract Facioscapulohumeral muscular dystrophy (FSHD) is a degenerative muscle disease caused by loss of epigenetic silencing and ectopic reactivation of the embryonic double homeobox protein 4 gene (DUX4) in skeletal muscle. The p38 MAP kinase inhibitor losmapimod is currently being tested in FSHD clinical trials due to the finding that p38 inhibition suppresses DUX4 expression in preclinical models. However, the role of p38 in regulating DUX4 at different myogenic stages has not been investigated. We used genetic and pharmacologic tools in FSHD patient-derived myoblasts/myocytes to explore the temporal role of p38 in differentiation-induced DUX4 expression. Deletion of MAPK14/11 or inhibition of p38α/β caused a significant reduction in early differentiation-dependent increases in DUX4 and DUX4 target gene expression. However, in MAPK14/11 knockout cells, there remains a differentiation-associated increase in DUX4 and DUX4 target gene expression later in differentiation. Furthermore, pharmacologic inhibition of p38α/β only partially decreased DUX4 and DUX4 target gene expression in late differentiating myotubes. In xenograft studies, p38α/β inhibition by losmapimod failed to suppress DUX4 target gene expression in late FSHD xenografts. Our results show that while p38 is critical for DUX4 expression during early myogenesis, later in myogenesis a significant level of DUX4 expression is independent of p38α/β activity.